Immunohistochemical analysis of a ruptured basilar top aneurysm autopsied 22 years after embolization with Guglielmi detachable coils. (25th July 2014) - Yuki, Ichiro; Spitzer, Daniel; Guglielmi, Guido; Duckwiler, Gary; Fujimoto, Motoaki; Takao, Hiroyuki; Jahan, Reza; Tateshima, Satoshi; Murayama, Yuichi; Vinuela, Fernando
Abstract : The authors report on the histologic and immunohistochemical analyses of a cerebral aneurysm embolized with platinum coils and with the longest observation period. A 58-year-old woman presenting with subarachnoid hemorrhage due to ruptured basilar top aneurysm was treated with Guglielmi detachable coils (GDC) 22 years ago. She was the 15th case since the GDC was introduced. After she died of unrelated causes, an autopsy and thorough histologic examination were performed. Gross examination revealed no adhesion between the aneurysm wall and the surrounding brain tissue. Histologic and immunohistochemical analyses demonstrated that the cavity of the aneurysm was filled with homogeneous collagenous fibrous tissue, while the neck was completely covered by a dense collagenous neointima and a smooth muscle cell layer. The unique histologic results of this case may contribute to a better understanding of the long-term evolution of the healing process in intracranial aneurysms successfully treated with the GDC.